Developmental expression of inhibitory synaptic long-term potentiation in the lateral superior olive - Kotak, Vibhakar C.; Sanes, Dan H. (Frontiers in Neural Circuits, 2014)
Principal neurons of the lateral superior olivary nucleus (LSO) respond selectively to interaural level differences (ILD). To perform this computation, LSO neurons integrate excitatory synaptic drive from the ipsilateral ear with inhibitory synaptic drive from the contralateral ear via the medial nucleus of the trapezoid body (MNTB). Previous research demonstrated that inhibitory terminals from the MNTB to the LSO are eliminated during development. Furthermore, MNTB synapses display an activity- and age-dependent long-term depression (iLTD) which may contribute to inhibitory synapse elimination. However, inhibitory synapses that are stabilized become stronger. Here, we asked whether MNTB synapses displayed activity-dependent strengthening. Whole-cell recordings were obtained from LSO neurons in a gerbil brain slice before and after hearing onset. The inhibitory MNTB afferents were stimulated at a low rate, similar to spontaneous discharge rates observed in vivo. The MNTB-evoked inhibitory responses were strengthened by 40-300% when synaptic activity was coupled with postsynaptic membrane depolarization, exogenous glutamate application, or activation of ipsilateral excitatory synaptic inputs. This inhibitory long-term potentiation (iLTP) was associated with increased spontaneous inhibitory postsynaptic current (IPSC) amplitude and frequency. One hour after iLTP induction, IPSCs could not be de-potentiated by the MNTB stimulation pattern that induces iLTD in control slices. iLTP could only be induced after hearing onset (>P12), and was blocked in the presence of a GABAB receptor antagonist. Together, these results suggest a developmental period during which the induction of iLTP depends on the conjoint activation of GABAB receptors and postsynaptic depolarization. We propose that iLTP may support stabilization of un-pruned MNTB connections and contribute to the emergence of ILD processing in the mature LSO.